一种注入式定子接地保护装置的检测系统及方法 (2023)
本发明公开了一种注入式定子接地保护装置的检测系统，所述系统包括：同步机物理模拟单元，所述同步机物理模拟单元通过升压变压器物理模拟单元与高压侧母线物理模拟单元相连接；所述同步机物理模拟单元的中性点侧与接地变压器物理模拟单元的原边侧相连接；所述接地变压器物理模拟单元的副边侧与负载电阻物理模拟单元相连接；注入式电源物理模拟单元与电压互感器物理模拟单元通过电流互感器物理模拟单元并联于负载电阻模拟单元两端；所述负载电阻物理模拟单元包括三个阻值不同的电阻，三个阻值不同的电阻为"π"形结构；所述电流互感器物理模拟单元与所述电压互感器物理模拟单元与录波器单元相连接。 The invention discloses a detection system of an injection-type stator grounding protection device. The system comprises: a synchronizer physical simulation unit, wherein the synchronizer physical simulation unit is connected to a high-voltage side bus physical simulation unit through a step-up transformer physical simulation unit; a neutral point side of the synchronizer physical simulation unite is connected to a primary side of a grounding transformer physical simulation unit; a secondary side of the grounding transformer physical simulation unit is connected to a load resistance physicalsimulation unit; an injection-type power supply physical simulation unit and a voltage transformer physical simulation unit are connected in parall